Screening of mango (Mangifera indica) germplasm for identification of sources resistant to mango malformation - Retracted - USHA, K; SINGH, OM PRAKASH; YADAV, ASHOK; G, NAYAN DEEPAK; B, SINGH; K, SHARMA D (The Indian Journal of Agricultural Sciences, 2019)
The study was carried out on 72 mango (Mangifera indica L.) cultivars and 107 mango F1 hybrids to group them based on degree of resistance to malformation during the period 2015-17. Intensity of malformation varied significantly among the mango cultivars and F1 hybrids under study. Out of 72 mango cultivars and 107 F1 hybrids studied, only three cultivars namely Bhadauran, Ilaichi and Arka Nilanchal were found to be completely free from the mango malformation disease (0%) and were categorised as resistant. Minimum disease incidence (50%) to mango malformation. The resistant and tolerant cultivars and F1 hybrids observed in the current study can be used as parents in future breeding programmes for developing a variety resistant to mango malformation.